Proteomics-based screening of AKR1B1 as a therapeutic target and validation study for sepsis-associated acute kidney injury - Li, Lei; Ling, Zaiqin; Wang, Xingsheng; Zhang, Xinxin; Li, Yun; Gao, Guangsheng (PeerJ, 2024)
Background Sepsis and sepsis-associated acute kidney injury (SA-AKI) pose significant global health challenges, necessitating the development of innovative therapeutic strategies. Dysregulated protein expression has been implicated in the initiation and progression of sepsis and SA-AKI. Identifying potential protein targets and modulating their expression is crucial for exploring alternative therapies. Method We established an SA-AKI rat model using cecum ligation perforation (CLP) and employed differential proteomic techniques to identify protein expression variations in kidney tissues. Aldose reductase (AKR1B1) emerged as a promising target. The SA-AKI rat model received treatment with the aldose reductase inhibitor (ARI), epalrestat. Blood urea nitrogen (BUN) and creatinine (CRE) levels, as well as IL-1β, IL-6 and TNF-α levels in the serum and kidney tissues, were monitored. Hematoxylin-eosin (H-E) staining and a pathological damage scoring scale assessed renal tissue damage, while protein blotting determined PKC (protein kinase C)/NF-κB pathway protein expression. Result Differential proteomics revealed significant downregulation of seven proteins and upregulation of 17 proteins in the SA-AKI rat model renal tissues. AKR1B1 protein expression was notably elevated, confirmed by Western blot. ARI prophylactic administration and ARI treatment groups exhibited reduced renal injury, low BUN and CRE levels and decreased IL-1β, IL-6 and TNF-α levels compared to the CLP group. These changes were statistically significant (P < 0.05). AKR1B1, PKC-α, and NF-κB protein expression levels were also lowered in the ARI prophylactic administration and ARI treatment groups compared to the CLP group (P < 0.05). Conclusions Epalrestat appeared to inhibit the PKC/NF-κB inflammatory pathway by inhibiting AKR1B1, resulting in reduced inflammatory cytokine levels in renal tissues and blood. This mitigated renal tissue injuries and improved the systemic inflammatory response in the severe sepsis rat model. Consequently, AKR1B1 holds promise as a target for treating sepsis-associated acute kidney injuries.
Keywords: Proteomics; AKR1B1; Sepsis; Acute kidney injury; Therapy